저농도 이산화탄소 포집용 활성탄소섬유 흡착제의 질소작용기 함침연구 - 황수현(Su-Hyun Hwang); 김동우(Dong-Woo Kim); 정동원(Dong-Won Jung); 조영민(Young-Min Jo) (한국대기환경학회지, 2016)
Activated carbon fibers (ACFs) for $CO_2$ adsorption were prepared from polyacrylonitrile (PAN) fiber through the systematic processes such as oxidation, activation and amination with the focus on the formation of nitration functional groups. Textural analysis of test samples revealed the decrease of specific surface area and pore volume by chemical activation including amination. The ratio of micropores to the total volume was 0.85 to 0.91, which was high enough with the pore size of 1.57 to 1.77 nm. Nitrogen compounds such as imine, pyridine and pyrrole presenting favorable interforces to $CO_2$ molecules were formed throughout the whole preparation steps. The aminated ACF adsorbent showed the enhanced adsorption capacity, 0.40 mmol/g for low-level $CO_2$ flow (3000 ppm) at room temperature. Selectivity of $CO_2$ against dry air ($O_2$ & $N_2$) also increased from 1.00 to 4.66 by amination.